3D macroporous architecture of self-assembled defect-engineered ultrathin g-C3N4 nanosheets for tetracycline degradation under LED light irradiation. (January 2021) - Ghosh, Utpal; Majumdar, Ankush; Pal, Anjali
Graphical abstract: Highlights: Ethylene glycol assisted synthesis of 3D macroporous g-C3 N4 structure is reported. The structure is composed of 2D defect engineered nanosheets with an average thickness of 7 nm. The Nitrogen vacancy induced photocatalyst possess improved light absorption capacity. It showed an enhanced degradation efficiency toward tetracycline under LED illumination. Abstract: Herein, the facile fabrication of a novel 3D macroporous structure of graphitic carbon nitride composed of self-assembled 2D nitrogen vacancy engineered nanosheets have been reported. The synthesis of the defect-engineered structure was achieved upon the addition of ethylene glycol during the solid-state synthesis process. The photocatalyst was characterized through a wide range of characterization techniques. The macroporous structure exhibited superior photocatalytic efficiency towards tetracycline antibiotic degradation under LED light illumination. The defect-engineered material (4EGCN) exhibited a 3.3-fold superior degradation rate coefficient of 0.010 min −1, compared to the degradation rate coefficient (0.003 min −1 ) of the bulk counterpart. This superior photocatalytic performance could be accredited to the extended visible light extraction efficiency, increased suppression efficacy of charge carriers, and porous structure. Moreover, the photocatalyst showed excellent stability even after five cycles of photocatalytic tetracycline degradation. Further, a probable degradation mechanism has been proposed according to the observations of the radical scavenging experiments.